2011
DOI: 10.1111/j.1399-3046.2011.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular and tubular function following orthotopic liver transplantation in children treated with tacrolimus

Abstract: The aim of this study was to analyze the impact of TAC on medium term (three-yr follow-up) renal function in pediatric liver transplant (OLT) recipients. Glomerular and tubular indices were retrospectively analyzed in 24 consecutive OLT pediatric recipients on TAC. CrCl increased significantly each month post-OLT (p = 0.003), with a trend toward significance between pre-OLT and 36 months (p = 0.17). There was no correlation between CrCl and TAC troughs (p = 0.783). Sixteen percent of patients had CrCl <60 mL/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…We also know that ESKD represents only a small proportion of all cases of CKD, and the low ESKD incidence rate reported in this study should not diminish the importance of detecting and treating long-term kidney dysfunction in this population, as the burden of earlier stages of disease is certainly much higher. This prevalence of CKD has been described in multiple small studies of pediatric LT recipients, with the rate of CKD reported as high as 31%, depending on the definition of CKD and duration of follow-up (10, 2025). Additionally, non-transplant studies consistently show that the natural history of CKD in children is characterized by a steady decline in kidney function over time.…”
Section: Discussionmentioning
confidence: 83%
“…We also know that ESKD represents only a small proportion of all cases of CKD, and the low ESKD incidence rate reported in this study should not diminish the importance of detecting and treating long-term kidney dysfunction in this population, as the burden of earlier stages of disease is certainly much higher. This prevalence of CKD has been described in multiple small studies of pediatric LT recipients, with the rate of CKD reported as high as 31%, depending on the definition of CKD and duration of follow-up (10, 2025). Additionally, non-transplant studies consistently show that the natural history of CKD in children is characterized by a steady decline in kidney function over time.…”
Section: Discussionmentioning
confidence: 83%
“…Kivela also reported a high prevalence of CKD after orthotopic liver transplantation in children with cyclosporin immunosuppression . A recent longitudinal study from Geneva of 24 pediatric liver transplant recipients on tacrolimus suggests that the prevalence of CKD may not be related to the choice of the calcineurin inhibitor . In this cohort, 39% of patients had a GFR <90 mL/min/1.73 m 2 at the time of transplantation.…”
Section: Renal Dysfunction After Pediatric Solid Organ Transplantationmentioning
confidence: 62%
“…The particular strength of Stelle's study is its longitudinal nature and the inclusion of other nephrological parameters such as proteinuria and hypertension . Interestingly, albeit that tacrolimus‐related nephrotoxicity is considered as the etiological factor for the development of progressive CKD , there was no correlation between the tacrolimus exposure (measured as trough level) and the measured GFR in the study from Geneva . The etiology of the CKD is probably multifactorial.…”
Section: Renal Dysfunction After Pediatric Solid Organ Transplantationmentioning
confidence: 99%
“…Although these data are compelling, the prevalence of CV risk factors and target organ damage reported here should be interpreted with caution. First, the prevalence of renal impairment is higher than in most other reports, which may skew results . Second, exposure to CNIs is difficult to quantify based on simple trough‐level measurements.…”
mentioning
confidence: 89%
“…In addition, one‐third exhibited evidence of 1 or 2 CV risk factors that are less well studied in children: microinflammation and anemia. Finally, nearly 41.6% of patients had an estimated glomerular filtration rate (eGFR) <90 mL/minute/1.73 m 2 , a known adverse effect of CNIs . Therefore, in total, nearly 30% of these pediatric recipients had at least 1 CV risk factor and nearly 60% had 2 or more.…”
mentioning
confidence: 99%